Knowledge and attitudes about influenza vaccination in rheumatic diseases patients - Figueroa Parra, Gabriel; Esquivel Valerio, Jorge Antonio; Santoyo Fexas, Leticia; Moreno Salinas, Andrea; Gamboa Alonso, Carmen Magdalena; De Leon Ibarra, Ana Laura; Galarza Delgado, Dionicio Ángel (Taylor and Francis, 2020)
Patients with rheumatic diseases (RD) have a higher risk of morbidity and mortality from vaccine preventable infections attributed to disease activity, comorbidities, immunosuppressive therapy, and other factors. Vaccines are one of the safest and most effective public health interventions. The aim of this study was to investigate knowledge and attitudes about influenza vaccination as factors influencing vaccine uptake and hesitancy in a population with RD. A descriptive cross-sectional study was designed. A self-administered questionnaire surveyed age, RD diagnosis, ten questions about the uptake, safety and efficacy of influenza vaccine, knowledge of cost-free availability, and the relationship between influenza vaccination and RD. A total of 223 questionnaires were filled; 79.8% of patients were vaccinated for influenza at least once. Uptake by diagnosis was 80.3% in rheumatoid arthritis, 76.2% in osteoarthritis, 86.7% in lupus, 73.9% in other auto-immune diseases (AID), and 60% in other non-AID; 83.9% of patients considered influenza vaccine as safe and effective. From those who had never been vaccinated, 26.7% of patients did not consider influenza vaccine safe and effective vs. 13.5% among patients who had been vaccinated (P = .032). Only 7.6% considered that RD patients could not be vaccinated; 11.7% thought that influenza vaccine would worsen their RD symptoms. This study showed that concerns about safety, efficacy, side effects, fear of the vaccine, and knowledge of cost diminished vaccine uptake. These are factors related to confidence, complacency, and convenience as components of vaccine hesitancy that affect influenza vaccination in RD patients.